Comparison of Optimized Long Echo Time STEAM and PRESS Proton MR Spectroscopy of Lipid Olefinic Protons at 3 Tesla - Bingolbali, Ayhan; Fallone, B. Gino; Yahya, Atiyah (WILEY, 2015)
PurposeTo investigate the response of lipid olefinic protons (approximate to 5.35 ppm) as a function of STEAM (Stimulated Echo Acquisition Mode) mixing time (TM), and echo time (TE), to find values that resolve the olefinic resonance from water in vivo while retaining sufficient olefinic signal. Materials and MethodsPRESS (Point RESolved Spectroscopy) and STEAM experiments with varying timing parameters (TE and also TM for STEAM) were conducted on nine oils (almond, canola, cod liver, corn, linseed, peanut, sesame, sunflower, and walnut oil), and on vertebral bone marrow in vivo at 3 Tesla (T). Olefinic and methylene (methyl+methylene in vivo) peak areas were measured. ResultsOptimal STEAM parameters were found to be TM=20 ms and TE=100 ms. The STEAM olefinic/methylene area ratios (ranging between 0.1 and 0.4) calculated for each oil correlated well with ratios deduced from oil compositions in the literature (R-2=0.975). The optimized STEAM sequence resolved the olefinic peak from water in vivo and yielded on average 1.91 times more olefinic signal compared with a previously optimized PRESS (TE=200 ms) sequence tailored for the same purpose. Olefinic/(methyl+methylene) area ratios obtained with optimized STEAM and PRESS in vivo were linearly correlated (R-2=0.972). ConclusionA STEAM sequence with TE=100 ms and TM=20 ms provides an alternative to the previously optimized PRESS (TE=200 ms) sequence for determining relative amounts of lipid unsaturation at 3T.J. Magn. Reson. Imaging 2013. (c) 2013 Wiley Periodicals, Inc. J. Magn. Reson. Imaging 2015;41:481-486.(c) 2013 Wiley Periodicals, Inc.
Keywords: magnetic resonance spectroscopy; PRESS; STEAM; spinal bone marrow; olefinic protons; lipid unsaturation; FATTY-ACIDS; LIVER FAT; H-1 MRS; UNSATURATION; Radiology, Nuclear Medicine & Medical Imaging